Exploring the impact of social influence on parents’ intention to use institutional childcare: a cross-sectional study - Bo Yu; Difan Zhang; Yin Sun; Yuna Yao; Yingji Li; Huiling Hu (BMC Health Services Research)
Abstract Background China is actively responding to low birth rates by developing childcare institutions to alleviate the parenting pressures on families. However, despite strong childcare demand, the enrollment rate remains low. Few studies have explored the role of social influence in parents' childcare decisions. Therefore, this study will construct a research model to explore the mechanisms of social influence on parents' intentions to use childcare institutions. Methods This study used parents of infants and toddlers in mainland China as the study population. Questionnaires were collected through electronic surveys created on a professional website, with 554 responses gathered through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and Importance-Performance Map Analysis (IPMA). Results The results indicate that perceived benefits are the significant driving variable for parents' intention to use childcare institutions, while price sensitivity and perceived risk are significant barriers. Normative influence and perceived childcare policy significantly affect perceived benefits and price sensitivity, while informational influence has a significant positive effect on perceived risk. Additionally, the Importance-Performance Map Analysis (IPMA) shows that improvements should focus more on price sensitivity given the current low performance. Conclusions These findings provide insights for childcare policymakers and institutional childcare managers and will generate a management basis for developing China’s childcare service industry.